FISIOTERAPI DAN TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION, SHORTWAVE DIATHERMY DAN TERAPI LATIHAN PADA OSTEOARTHRITIS GENU SINISTRA - Tastaftian, Fadli (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Knee osteoarthritis is a progressive degenerative joint disorder commonly affecting adults and the elderly, characterized by pain, stiffness, reduced joint range of motion, muscle weakness, and functional limitations. Physiotherapy modalities such as Transcutaneous Electrical Nerve Stimulation (TENS), Short Wave Diathermy (SWD), and therapeutic exercise are applied to reduce symptoms and improve functional movement in patients with osteoarthritis. Objective: To describe the physiotherapy management using TENS, SWD, and therapeutic exercise in a patient with left knee osteoarthritis. Methods: A case study was conducted on a 61-year-old female patient diagnosed with grade 3 left knee osteoarthritis. Evaluation tools included the Visual Analog Scale (VAS) for pain assessment, a goniometer for joint range of motion, Manual Muscle Testing (MMT) for muscle strength, and the WOMAC scale for functional ability. The intervention was provided over four therapy sessions. Results: After four physiotherapy sessions, there was a reduction in tenderness and movement pain, an increase in left knee joint range of motion, improved extensor muscle strength, and enhanced functional ability based on WOMAC scores. Conclusion: The combination of TENS, SWD, and therapeutic exercise is effective in reducing pain, improving joint mobility, muscle strength, and functional activity in patients with left knee osteoarthritis